Sintering of compound nonwovens by forced convection of hot air. (October 2016) - Staszel, C.; Sett, S.; Yarin, A.L.; Pourdeyhimi, B.
Graphical abstract: Highlights: Forced convection through nonwovens was explored experimentally and theoretically. Transient temperature field was predicted and validated experimentally. Nonwovens were sintered and stiffened by forced convection of air. Stiffness of the sintered nonwovens was measured. Abstract: Sintering and interlocking of model nonwoven materials composed of a mixture of polycaprolactone (PCL) and polyacrylonitrile (PAN) fibers by means of forced convection of hot air through their pores is studied experimentally and theoretically. PCL has a much lower melting point than PAN, and the air temperature was sufficiently high to melt the former, while the latter stayed solid. These molten PCL fibers became a binder and conglutinated the PAN matrix, enhancing stiffness. This was demonstrated by measuring the effect of heat treatment on the resulting Young's modulus of these compound nonwovens, as well as by the corresponding micro-morphological changes revealed by scanning electron microscopy. It was also shown that heating past the melting point of the binding fibers (PCL) would not further increase stiffness of the nonwovens, neither would heating for longer periods of times. A theoretical model describing the heating process was developed and tested experimentally. The model was verified using poly(ethylene terephthalate) PET nonwovens, which revealed good agreement of the data with the theoretical predictions.